Nano- and Micro-Encapsulation Techniques and Applications - GÖNCÜ, BEYZA SERVET; Göncü, Beyza Servet; YÜCESAN, EMRAH; Yücesan, Emrah (My University, 2021)
Microencapsulation has been the most frequently used technique for several different disciplines such as cell-based therapies and/or transplantation. Technology is based on the idea of combining and coating material or isolating it from an external source. Microencapsulation may be performed with different materials and, among natural biocompatible materials, alginate-based microencapsulation technique is the most appropriate material for microencapsulation. The structural components of alginate materials are the derivatives of alginic acid, which is found in brown algae as an intercellular gel matrix. This alginate is preferred for clinical applications due to its safety in human studies. Therefore, the choice and the combined system need to be carefully optimized to achieve biocompatible application through cell microencapsulation especially for long term. Specifications of alginate such as primary source, isolation process, viscosity, and purity contribute to improve its biocompatibility. Clinically, cell microencapsulation is the major contribution to the field of transplantation by its technique and additionally provides local immune isolation. This chapter discusses the potential benefits of clinically suitable alginates and their applications. This promising technology may highlight its considerable potential for patients that require transplantation and/or replacement therapy in the future.